Implementasi Kebijakan Badan Usaha Milik Desa (BUMDes) di Desa Sindangheula Kecamatan Pabuaran - Pangestu, Yoga (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2024)
Every public policy will not be separated from policy implementation. Policy implementation becomes one of the sacred things in a policy, because implementation will show the quality of the formation of a policy, in this case the BUMDes Policy. As in general, the BUMDes policy is formulated by the central government. However, matters related to the implementation of the BUMDes policy are still regulated and managed by the village government. To find out things related to the implementation of this BUMDes policy, it can be seen from 4 aspects namely; Implementing Organization, Target Groups, Idealize Policy and Environment Factors. Many organizations are involved in the implementation of BUMDes policy, ranging from the central government, local government, village government, to community groups. In the establishment of BUMDes, the community is involved because the target of the BUMDes policy is the community itself. BUMDes is present with the aim of reducing unemployment andmaking a profit. Community support and demands answer all the things that need to be done in BUMDes. If these 4 aspects are able to be carried out properly, it can be said that the implementation of the BUMDes policy is declared successful.